SDSS-IV MaNGA: drivers of stellar metallicity in nearby galaxies. Issue 4 (9th October 2021) - Neumann, Justus; Thomas, Daniel; Maraston, Claudia; Goddard, Daniel; Lian, Jianhui; Hill, Lewis; Domínguez Sánchez, Helena; Bernardi, Mariangela; Margalef-Bentabol, Berta; Barrera-Ballesteros, Jorge K; Bizyaev, Dmitry; Boardman, Nicholas F; et al.
ABSTRACT: The distribution of stellar metallicities within and across galaxies is an excellent relic of the chemical evolution across cosmic time. We present a detailed analysis of spatially resolved stellar populations based on >2.6 million spatial bins from 7439 nearby galaxies in the Sloan Digital Sky Survey-IV (SDSS-IV) Mapping Nearby Galaxies at APO (MaNGA) survey. To account for accurate inclination corrections, we derive an equation for morphology-dependent determination of galaxy inclinations. Our study goes beyond the well-known global mass–metallicity relation and radial metallicity gradients by providing a statistically sound exploration of local relations between stellar metallicity [Z/H], stellar surface mass density Σ⋆, and galactocentric distance in the global mass–morphology plane. We find a significant resolved mass density–metallicity relation rΣ _ZR for galaxies of all types and masses above 10^9.8 M_ . Different radial distances make an important contribution to the spread of the relation. Particularly, in low- and intermediate-mass galaxies, we find that at fixed Σ⋆ metallicity increases with radius independently of morphology. For high masses, this radial dependence is only observed in high Σ⋆ regions of spiral galaxies. This result calls for a driver of metallicity, in addition to Σ⋆ that promotes chemical enrichment in the outer parts of galaxies more strongly than in the inner parts. We discuss gas accretion, outflows, recycling, and radial migration as possible scenarios.